Orientasi Pelayanan Bimbingan Konseling yang Inklusif: Meningkatkan Akses dan Kualitas Layanan untuk Semua Siswa - Ayu Hayati Lubis; Yarmis Syukur; Dina Sukma (CV. ITTC INDONESIA, 2024)
Inclusive guidance and counseling (CDC) services play a vital role in creating an equitable educational environment that supports the diversity of students’ needs. This article aims to explore how an inclusive guidance and counseling service orientation can improve access and quality of services for all students, especially those facing social, emotional, and academic challenges. In an increasingly diverse educational context, inclusive guidance and counseling services must take into account students’ diverse backgrounds, including cultural differences, physical conditions, and special needs. With an approach based on the principle of equality, guidance and counseling services can ensure that every student, without exception, gets the opportunity to develop optimally.